Spatial and Bioaccumulation of Heavy Metals in a Sheep-Based Food System: Implications for Human Health - Florin-Ioan Fechete; Maria Popescu; Sorin-Marian Mârza; Loredana-Elena Olar; Ionel Papuc; Florin-Ioan Beteg; Robert-Cristian Purdoiu; Andrei Răzvan Codea; Caroline-Maria Lăcătuș; Ileana-Rodica Matei; Radu Lăcătuș; Adela Hoble; et al. (Toxics, 2024)
Heavy metal contamination in agricultural soils presents serious environmental and health risks. This study assessed the bioaccumulation and spatial distribution of nickel, cadmium, zinc, lead, and copper within a sheep-based food chain in the Baia Mare region, Romania, which includes soil, green grass, sheep serum, and dairy products. Using inductively coupled plasma mass spectrometry (ICP-MS), we analyzed the concentrations of these metals and calculated bioconcentration factors (BCFs) to evaluate their transfer through trophic levels. Spatial analysis revealed that copper (up to 2528.20 mg/kg) and zinc (up to 1821.40 mg/kg) exceeded permissible limits, particularly near former mining sites. Elevated lead (807.59 mg/kg) and cadmium (2.94 mg/kg) were observed in industrial areas, while nickel and cobalt showed lower concentrations, but with localized peaks. Zinc was the most abundant metal in grass, while cadmium transferred efficiently to milk and cheese, raising potential health concerns. The results underscore the complex interplay between soil properties, contamination sources, and biological processes in heavy metal accumulation. These findings highlight the importance of continuous monitoring, risk assessment, and mitigation strategies to protect public health from potential exposure through contaminated dairy products.